Behavioral and Molecular Responses to Exogenous Cannabinoids During Pentylenetetrazol-Induced Convulsions in Male and Female Rats - Zirotti Rosenberg, Antonella; Méndez-Ruette, Maxs; Gorziglia, Mario; Alzerreca, Benjamín; Cabello, Javiera; Kaufmann, Sofía; Rambousek, Lukas; Iturriaga Jofré, Andrés; Wyneken, Ursula; Lafourcade, Carlos A. (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a disabling, chronic brain disease, affecting ~1% of the World’s population, characterized by recurrent seizures (sudden, uncontrolled brain activity), which may manifest with motor symptoms (e.g. convulsions) or non-motor symptoms. Temporal lobe epilepsies (TLE) compromising the hippocampus are the most common form of focal epilepsies. Resistance in ~ 1/3 of epileptic patients to the first line of treatment, i.e., antiepileptic drugs (AEDs), has been an important motivation to seek for alternative treatments. Among these, the plant Cannabis sativa (commonly known as marihuana) or compounds extracted from it (cannabinoids) have gained widespread popularity. Moreover, sex differences have been proposed in epilepsy syndromes and in cannabinoid action. In the hippocampus, cannabinoids interact with the CBR1 receptor whose membrane levels are regulated by Beta Arrestin-2, a protein that promotes its endocytosis and causes its downregulation. In this paper we evaluate the modulatory role of a synthetic exogenous cannabinoid (WIN 55212-2) on behavioral convulsions and on the levels of CBR1 and Beta Arrestin-2 in female and male adolescent rats after a single injection of the proconvulsant pentylenetetrazol (PTZ). As epilepsies can have a considerable impact on synaptic proteins that regulate neuronal toxicity, plasticity and cognition, we also measured the levels of key proteins markers of excitatory synapses, in order to examine whether exogenous cannabinoids may prevent such pathologic changes after acute seizures. We found that the exogenous administration of WIN 55212-2 prevented convulsions of medium severity in females and males and increased the levels of phosphorylated CamKII in the hippocampus. Furthermore, we observed a higher degree of colocalization between CB1R and Beta Arrestin-2 in the granule cell layer. We conclude that WIN 55212-2 may be effective when treating seizures to ameliorate certain clinical manifestations (e.g. medium severity seizures). Some of the molecular changes induced by WIN 55212-2 (e.g. higher levels of phosphorylation and increased colocalization of CB1R wih Beta Arrestin-2) may be part of a homeostatic response to maintain the appropriate levels of excitability in the circuit, or as a mechanism to reduce neurotoxicity.